The Kano model analysis of features for mobile security applications. Issue 78 (September 2018) - Yao, Mei-Ling; Chuang, Ming-Chuen; Hsu, Chun-Cheng
Abstract: The Google Play app store is providing more than 200 mobile security applications (MSAs) with abundant features. This study consolidates and extracts 12 main mobile security and antivirus features out of the top 25 MSA vendors to find out how users evaluate and classify quality attributes for these features with the Kano Model two-dimensional questionnaire. The analysis result shows that all features could be classified as either one-dimensional or indifferent quality. These 12 features could be further grouped into 5 quality types (O, OA, OI, IO and I) based on SI and DSI values assigned to each feature for its impact on customer satisfaction. Overall, the top four features with greater impact on customer satisfaction are "malware prevention", "safe browsing", "parental control" and "privacy protection". The MSA vendors should emphasize these 4 features. The "secure app advisor" and "app lock" may enjoy less attention as they bear little impact on customer satisfaction. The "data backup", "garbage file cleanup", "Wi-Fi security", "message and call filter", "remote wipe" and "remote lock and locate" have the higher impact on increasing customer satisfaction than reducing dissatisfaction. For MSA vendors with above average quality, they have to put more design efforts on these features to gain more customer satisfaction. Female users pay more attention to "remote lock and locate" and "Wi-Fi security" while users with little technological knowledge focus on "garbage file cleanup", "remote lock and locate" and "secure app advisor".